(3MOjbI GdCRgGQ aj TQM eGgjI GdYTH hGdYbGQs - (3bGSe Hf eMeO Hf EHQGgje GdhRjQ GdZSGfj, GdhRjQ,J (B1019 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdYdhe CfaS CNdGb Hdg JRjO HGdEfaGb , CMb eG CJMaJ Gdgee s
(3BNQgG (B:s
(3fGaY ef UdGHI GdWMGd , HOdg EPG hLhOg LGhTjQ s
(3QJHg Ydi MQha GdgLGAs
(3bOeg Edi GdSdWGf GdeZQHi GdCbUi CHi GdYHGS CMeO GdefUhQ Hf eMeO GdegOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B182s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs